A dynamic watershed model for determining the effects of transient storage on nitrogen export to rivers. Issue 10 (6th October 2014) - Chen, Dingjiang; Hu, Minpeng; Dahlgren, Randy A.
Abstract Legacy anthropogenic nitrogen (N) has been suggested as a major cause for increasing riverine N exports despite significant declines in anthropogenic N inputs in many regions. However, little quantitative knowledge exists concerning the contribution of the legacy N pool to riverine N export. This study developed a dynamic watershed N delivery model to address the role of transient storage of anthropogenic N inputs on riverine N flux. Employing simple mass balance and equivalent substitution rules, the model expresses the transient storage of legacy N mass with a term that combines the previous one year's riverine total N (TN) flux, relevant explanatory variables, and unknown parameters, enabling us to inversely calibrate the model parameters from measurable variables using Bayesian statistics. The model efficacy was demonstrated through application to the Yong'an River watershed in eastern China based on a 31 year record (1980–2010) of riverine TN fluxes. The model can quantify annual transient storage of legacy N and its resulting contribution to annual riverine N flux. The model also allows partitioning of the complete long‐term mass balance for the fate (e.g., transient storage, riverine export, and loss/retention by denitrification, biomass uptake and wood product export) of annual anthropogenic N inputs. To further improve the model, various N input‐output processes can be specified and long‐term measurements of N fates are required to further verify the model results. This study demonstrates the need to consider transient storage effects as an improvement to current watershed models and for developing and assessing N pollution control measures.